Individualization of post-mastectomy radiotherapy and regional nodal irradiation based on treatment response after neoadjuvant chemotherapy for breast cancer - Krug, David; Wenz, Frederik (Strahlentherapie und Onkologie, 2018)
PurposeTo review the evidence regarding post-mastectomy radiotherapy (PMRT) and regional nodal irradiation (RNI) after neoadjuvant chemotherapy (NACT) for breast cancer, with a special focus on individualization of adjuvant radiotherapy based on treatment response.MethodsA systematic literature search using the PubMed/Medline database was performed. We included prospective and retrospective reports with a minimum of 10 patients that had been published since 1st January 2000, and provided clinical outcome data analyzed by treatment response and radiotherapy.ResultsOut of 763 articles identified via PubMed/Medline and hand search, 68 full text-articles were assessed for eligibility after screening of title and abstract. 13 studies were included in the systematic review, 9 for PMRT and 5 for RNI. All included studies were retrospective reports.ConclusionsThere is a considerable lack of evidence regarding the role of adjuvant radiotherapy and its individualization based on treatment response after NACT. Results of prospective randomized trials such as NSABP B‑51/RTOG 1304 and Alliance A11202 are eagerly awaited.
Gesehen am 30.10.2019